'Everything transforms and nothing changes'1: Strategies of adapting The Transformers toys into a TV series. (1st March 2022) - Wolski, Michał
The Transformers franchise is one of the highest-grossing intellectual properties of all time, mostly because of the successful marketing and advertising strategy called toyesis (Jason Bainbridge's term). Toyesis is a kind of symbiosis between toy market and cultural products, such as cartoons and comics, in which the latter creates an urge of having a new toy, sales of which in turn help finance the whole system. A series of legal decisions and regulations in the 1980s United States made an uncontrolled toy advertising in TV shows possible, and the Transformers franchise (and its owner, the Hasbro company) exploited it without hesitation. But to do so, their contractors (writers, animation studios, etc.) encountered an issue regarding how one can adapt a toy into a cartoon. The article focuses on the strategies of remediation, reconfiguration and incorporation of a toy material into storytelling media, especially into a cartoon. Using Marsha Kinder's concept of entertainment system, it also examines which strategies reinforced the advertising potential of this material, often without children realizing that they, in fact, watch a sophisticated commercial.